'It's all bollocks!' and other critical standpoints on the UK Government's vision of global citizenship. Issue 4 (4th July 2017) - Griffiths, Mark
ABSTRACT: The UK Government's International Citizen Service (ICS) sends volunteers abroad to 'fight global poverty' as 'global citizens'. Perhaps unsurprisingly, the construction of development on the ICS programme forecloses important political and historical contexts, resulting in a model of global citizenship we might term 'soft'. This article presents data from interviews with ICS volunteers with a specific methodological concern of recognizing the agency of young people and allowing their responses to lead discussion. The outcome is a range of themes across the data that critique the Government's model of citizenship and, I argue, shows the volunteers to be 'critical' global citizens. I then ask whether we can consider this a mode of resistance. I conclude with a final data set that – the case is made – presents an imperative to allow these volunteers to have their perspectives on historical and contemporary North–South relations recognized as a critical mode of global citizenship.